2017
DOI: 10.1071/an16212
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weight and age on pregnancy rates in Brahman heifers in northern Australia

Abstract: The performance of Brahman heifers at their first mating as yearlings (4-year groups of ~100 per year) grazing on improved pasture in the Douglas Daly region and as 2 year olds (3-year groups of ~100 per year) grazing on native pasture in the Victoria River District was studied. The relationships between pre-mating weight and pregnancy rate were established for Brahman heifers mated as yearlings on improved pasture, and as 2 year olds on native pasture with pre-mating weights recorded in late October/early Nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
4
2
0
Order By: Relevance
“…Overall, the parameter that explained the greatest variation for occurrence of pregnancy was PM.LW, which was, in general, greater for the NW compared with EW heifers. This is consistent with previous studies which have found that the most important factor affecting pregnancy rates of maiden heifers is PM.LW [ 35 , 36 ]. This outlines the long-term consequence of first dry season supplementation and WW on pregnancy percentage, a practical objective of this experiment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, the parameter that explained the greatest variation for occurrence of pregnancy was PM.LW, which was, in general, greater for the NW compared with EW heifers. This is consistent with previous studies which have found that the most important factor affecting pregnancy rates of maiden heifers is PM.LW [ 35 , 36 ]. This outlines the long-term consequence of first dry season supplementation and WW on pregnancy percentage, a practical objective of this experiment.…”
Section: Discussionsupporting
confidence: 93%
“…It suggests that two-year-old heifers need to have PM.LW of approximately 300 kg in October/November to achieve approximately 80% probability of pregnancy (67.1–90.3% for a 95% confidence interval), regardless of WW. Schatz and Hearnden [ 35 ] developed a similar model using data collected at the same location as this experiment. The authors proposed a target LW (curfew) of 253 kg measured in October/November would result in an 80% of pregnancy for two-year-old heifers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, age, if available, interacts with LW as shown in Figure 2 and Tables 1 and 4 early in reproductive life, whereas later reproduction performance during the 3 rd to 5 th parities is associated with fairly constant LWs (Table 5 and Vera et al, 1993) if the nutritional strategy persists. The current results are supported by data from very different, but still extensive, cattle systems of northern Australia (Schatz et al, 2011;Schatz and Hearnden, 2017) that were derived from several thousands of records pertaining to breeding heifers and cows in different physiological conditions that were also included for comparison in Figure 3. It should be noted that the "maiden" heifers of Schatz et al (2017) were at least one year older than their yearling heifers and showed much larger pregnancy rates at similar LW, thus adding support to the effect of the LW by Age interaction reported in the current results.…”
Section: Evolution Of Live Weights In Relation To Paritysupporting
confidence: 74%
“…The current results are supported by data from very different, but still extensive, cattle systems of northern Australia (Schatz et al, 2011;Schatz and Hearnden, 2017) that were derived from several thousands of records pertaining to breeding heifers and cows in different physiological conditions that were also included for comparison in Figure 3. It should be noted that the "maiden" heifers of Schatz et al (2017) were at least one year older than their yearling heifers and showed much larger pregnancy rates at similar LW, thus adding support to the effect of the LW by Age interaction reported in the current results. The coincidence between our estimates and that of Schatz et al (2017) with their yearling heifers is remarkable (Figure 3).…”
Section: Evolution Of Live Weights In Relation To Paritysupporting
confidence: 74%
“…It suggests that two-year-old heifers need to weigh approximately 300 kg at PM.LW in October/November to achieve 80% of pregnancy percentage, regardless of weaning weight. Schatz and Hearnden (2016) developed a similar model using data collected at the same location of this experiment. The authors proposed a target LW (curfew) of 253 kg measured in October/November would result in 80% conception rates for twoyear-old heifers.…”
Section: Reproductive Parametersmentioning
confidence: 99%